The Influence of Return on Assets, Return on Equity, Earnings Per Share, and Price Earning Ratio on The Share Price of PT Unilever Indonesia Tbk - Desi Sriwahyuni; Yasir Maulana (Indonesian Journal Of Business And Economics, 2022)
This study aims to determine the Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS), and Price Earning Ratio (PER) effect on Unilever's stock price. The secondary data used is PT Unilever Indonesia Tbk's financial report data, namely the period 2014 to 2019. The test results together with the variables Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS) and Price Earning Ratio (PER) has a significant influence on stock prices. The results of the partial analysis show that Return On Assets (ROA) and Return On Equity (ROE) have no effect on stock prices while Earning Per Share (EPS) and Price Earning Ratio (PER) have a positive and significant effect on stock prices. With a coefficient of determination of 82.8%, it means that the EPS and PER variables make a dominant contribution to Unilever's share price movements.